Intelligent Computer Mathematics 15th International Conference, CICM 2022, Tbilisi, Georgia, September 19-23, 2022, Proceedings - Buzzard, Kevin; Kutsia, Temur (Cham : Springer International Publishing : Imprint: Springer, 2022)
This book constitutes the refereed proceedings of the 15th International Conference on Intelligent Computer Mathematics, CICM 2022, held in Tbilisi, Georgia, in September 2022. The 17 full papers, 1 project/ survey paper, 4 short papers, and 2 abstracts of invited papers presented were carefully reviewed and selected from a total of 37 submissions. The papers focus on theoretical and practical solutions for these challenges including computation, deduction, narration, and data management.
Invited Talk -- Formalizations -- Digital Libraries and Mathematical Knowledge Management -- Theorem Proving and Expression Transformation -- Satisfiability, QBF, and SMT Solving -- Computer-Aided Teaching -- Datasets and system entries.
Keywords: Computational intelligence; Computational Intelligence